(untitled) («СОВРЕМЕННЫЕ ФИЛОЛОГИЧЕСКИЕ ПАРАДИГМЫ: ВЗАИМОДЕЙСТВИЕ ТРАДИЦИЙ И ИННОВАЦИЙ», 2025)
In the contemporary educational landscape, the integration of technology has become increasingly prevalent, transforming traditional teaching methodologies. This article explores the role of innovative educational technologies in teaching English as a second language. Through a review of literature, this paper examines various technologies such as mobile applications, gamification, virtual reality, and artificial intelligence, highlighting their potential benefits and challenges in enhancing English language acquisition. The article also discusses practical implications for educators and suggests future directions for research in this evolving field.